2019
DOI: 10.1161/hypertensionaha.119.13015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cardiovascular Dysregulation During Early Pregnancy After In Vitro Fertilization Cycles in the Absence of a Corpus Luteum

Abstract: Commonly used in vitro fertilization protocols produce pregnancies without a corpus luteum (CL), a major source of reproductive hormones. In vitro fertilization pregnancies without a CL showed deficient gestational increases of central (aortic) arterial compliance during the first trimester and were at increased risk for developing preeclampsia. Here, we investigated whether there was generalized impairment of cardiovascular adaptation in in vitro fertilization pregnancies without a CL compared with pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 45 publications
0
38
1
Order By: Relevance
“…However, endometrial preparation and absence of corpus luteum (CL) in frozen embryo transfer (FET) might predispose to adverse obstetric outcomes (hypertensive disorders, PE, postpartum hemorrhage, accreta, post‐term birth and macrosomia) 40–45 . Two recent studies showed that absence of CL in FET is associated with increased risk of PE and reduced aortic compliance, demonstrating the critical role of CL in the physiologic transformation of the maternal cardiovascular system in early gestation 46,47 . Since UtA‐PI is also related to maternal cardiovascular adaptation, the apparent contradiction in our finding of reduced UtA‐PI in the FET group, known to have higher risk for PE, may be explained by differences in maternal characteristics and the IVF technique used, which may be proxy markers for worse prepregnancy UtA‐PI and cardiovascular function 48,49 .…”
Section: Discussioncontrasting
confidence: 62%
“…However, endometrial preparation and absence of corpus luteum (CL) in frozen embryo transfer (FET) might predispose to adverse obstetric outcomes (hypertensive disorders, PE, postpartum hemorrhage, accreta, post‐term birth and macrosomia) 40–45 . Two recent studies showed that absence of CL in FET is associated with increased risk of PE and reduced aortic compliance, demonstrating the critical role of CL in the physiologic transformation of the maternal cardiovascular system in early gestation 46,47 . Since UtA‐PI is also related to maternal cardiovascular adaptation, the apparent contradiction in our finding of reduced UtA‐PI in the FET group, known to have higher risk for PE, may be explained by differences in maternal characteristics and the IVF technique used, which may be proxy markers for worse prepregnancy UtA‐PI and cardiovascular function 48,49 .…”
Section: Discussioncontrasting
confidence: 62%
“…However, it is likely that Doppler and the hormonal alterations described may have a multifactorial etiology, whereby intrinsic differences in the patient's characteristics (e.g., cardiovascular and metabolic function) as well as procedure-related factors may contribute to different extent, favoring or hampering placental and fetal development. In addition, recent work suggests that cardiovascular function is impaired and pre-eclampsia risk is elevated in women conceiving by IVF in the absence of a corpus luteum, which indicates the importance of the hormonal milieu in the early stages of pregnancy [16].…”
Section: Discussionmentioning
confidence: 99%
“…GDM is evidently related to the delivery of an infant with macrosomia, so the incidence of macrosomia is signi cantly higher for pregnant women with PCOS [29]. In addition, neonates of women with PCOS are at greater risk of neonatal complications, including perinatal mortality, prematurity, SGA, lower birth weight and higher NICU admission [31]. Current evidence also suggests that prepregnancy hormonal dysfunction, including hyperandrogenism, progesterone resistance and hyperinsulinism, impairs uterine placentation mechanisms, which may lead to a greater risk of adverse obstetric and neonatal outcomes [31].…”
Section: Discussionmentioning
confidence: 99%